Pengaruh Edukasi Video Gizi Seimbang Dalam Pencegahan Anemia Terhadap Pengetahuan Remaja Putri SMK Angkasa II Kalijati - Kiki Resqi Fitri Rosela; Fatimah Sari; Zesika Intan Navelia (Prodi Kebidanan Blora Program Diploma Tiga Poltekkes Kemenkes Semarang, 2026)
Anemia is a major health problem experienced by adolescent girls, with a high prevalence caused by various factors, particularly a lack of nutritional knowledge and low iron intake. Preventive efforts are crucial, especially health education delivered using engaging and accessible media. Video-based education, particularly animated formats, is considered effective in attracting attention, maintaining focus, and improving understanding among adolescents. This study aims to analyze the effect of balanced nutrition education using animated video media on adolescent girls' knowledge of anemia. This study used a quantitative quasi-experimental design with a pretest-posttest approach. A total of 42 female students at SMK II Angkasa Kalijati were selected using purposive sampling. Data collection was conducted through a structured questionnaire to assess knowledge levels before and after the intervention. Data analysis used the Shapiro-Wilk normality test, the Wilcoxon signed-rank test, and the Mann-Whitney test to evaluate differences in knowledge scores. The results showed a significant increase in knowledge after the intervention. The Mann-Whitney test showed a difference in pretest scores with a p-value of 0.001 and a posttest score with a p-value of 0.000. The Wilcoxon test also showed a significant increase in the mean rank with a p-value <0.05. These findings indicate that animated video media is very effective in increasing adolescent girls' knowledge about anemia prevention. In conclusion, health education using animated videos serves as an innovative and practical method to increase awareness and knowledge among adolescents, thus supporting efforts to reduce the prevalence of anemia.